Today's Relevance of Digital Control in Server- and Telecom Power Supplies - Schafmeister, Frank; Grote, Tobias; Figge, Heiko (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Adaptable AC Input Phase Switching - Ide, Peter; Schafmeister, Frank; Richter, Jörg; Pour, Barzin; Spesser, Daniel; Herke, Dietmar

Resistorless Precharging - Hufnagel, Michael; Schafmeister, Frank

Co-simulation of an interior permanent magnet synchronous motor with segmented rotor structure - Schulte, Christoph; Böcker, Joachim (IECON 2014 - 40th Annual Conference of the IEEE Industrial Electronics Society)

Switching strategy for Direct Model Predictive Control in power converter and drive applications with high switching frequency - Leuer, Michael; Böcker, Joachim (2015 6th International Conference on Automation, Robotics and Applications (ICARA))

Operating electrical high speed drives with pulse patterns of specific harmonic content - Peter, Klaus; Böcker, Joachim (2015 IEEE Energy Conversion Congress and Exposition (ECCE))

Self-optimizing Model Predictive Direct Torque Control for electrical drives - Leuer, Michael; Böcker, Joachim (2015 IEEE 24th International Symposium on Industrial Electronics (ISIE))

3D analytical model for estimation of eddy currentlosses in the magnets of IPM machine considering the reaction field of the induced eddy currents - Paradkar, Milind; Böcker, Joachim (2015 IEEE Energy Conversion Congress and Exposition (ECCE))

Voltage-Sequence-Control-Based High-Current Rectifier System - Solanki, Jitendra; Fröhleke, Norbert; Böcker, Joachim; Duppe, Gregor; Averberg, Andreas; Wallmeier, Peter (IEEE Transactions on Industry Applications)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Control and Systems Engineering

A comparison of on-board chargers for electric vehicles with variable DC-link voltage - Bolte, Sven; Speerschneider, Alexander; Fröhleke, Norbert; Böcker, Joachim (2015 IEEE International Conference on Smart Energy Grid Engineering (SEGE))

DCM detection for on-line adaption of control parameters for totem-pole PFC rectifier - Henkenius, Carsten; Fröhleke, Norbert; Böcker, Joachim; Figge, Heiko; Grote, Tobias (2015 IEEE International Conference on Industrial Technology (ICIT))

PFC-control for improved inductor utilization - Keuck, Lukas; Fröhleke, N.; Böcker, Joachim; Ziessler, A. (2015 17th European Conference on Power Electronics and Applications (EPE'15 ECCE-Europe))

Analysis of industrial microgrid power curves based on the theory of stochastic variables for control system development and component sizing - Vogt, T.; Keuck, L.; Fröhleke, N.; Böcker, Joachim; Kempen, S. (2014 International Conference on Advances in Green Energy (ICAGE))

Comparison of PWM AC chopper topologies - Hagemeyer, Marc; Solanki, Jitendra; Fröhleke, Norbert; Böcker, Joachim; Averberg, Andreas; Wallmeier, Peter (IECON 2014 - 40th Annual Conference of the IEEE Industrial Electronics Society)

Voltage utilization in Model Predictive Control for IPMSM - Leuer, Michael; Böcker, Joachim (2014 IEEE International Conference on Power Electronics, Drives and Energy Systems (PEDES))

Neuro control of a PFC rectifier for harmonic reduction at partial loads - Keuck, Lukas; Hemmelgarn, F.; Fröhleke, N.; Böcker, Joachim; Vohrmann, M.; Jungeblut, T.; Rückert, U. (2014 International Conference on Advances in Green Energy (ICAGE))

Wirkungsgradoptimale Regelung von permanenterregten Synchronmotoren in automobilen Traktionsanwendungen unter Berücksichtigung der magnetischen Sättigung - Peters, W.

High Power Factor High-Current Variable-Voltage Rectifiers - Solanki, J.

Multi-Objective Storage Operating Strategy for Industrial Microgrids - Vogt, Thorsten; Fröhleke, Norbert; Böcker, Joachim; Kempen, Stefan (German-Korean Symposium on Power Electronics)

Mehrziel-Speicherbetriebsstrategie für industrielle Microgrids - Vogt, T.; Fröhleke, N.; Böcker, Joachim; Kempen, S.

Implementation of Hybrid Filter for 12-Pulse Thyristor Rectifier Supplying High-Current Variable-Voltage DC Load - Solanki, J.; Fröhleke, N.; Böcker, Joachim

Optimum Efficiency Control of Interior Permanent Magnet Synchronous Motors in Drive Trains of Electric and Hybrid Vehicles - Peters, Wilhelm; Wallscheid, Oliver; Böcker, Joachim (European Conference on Power Electronics and Applications (EPE))

Real-time capable methods to determine the magnet temperature of permanent magnet synchronous motors—A review - Wallscheid, Oliver; Huber, Tobias; Peters, Wilhelm; Böcker, Joachim (IECON 2014-40th Annual Conference of the IEEE Industrial Electronics Society)

Determination of rotor temperature for an interior permanent magnet synchronous machine using a precise flux observer - Specht, Andreas; Wallscheid, Oliver; Böcker, Joachim (2014 International Power Electronics Conference (IPEC-Hiroshima 2014-ECCE ASIA))

Adaptable AC Input Phase Switching for Optimum Utilization of Various Grid Configurations supplying Power Electronic Converters and EV/HEV On Board Chargers - Schafmeister, Frank; Ide, Peter; Richter, Jörg (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

A Soft-Switching Interleaved DC-DC Converter with Integrated Magnetics for High Voltage Battery Charger - Li, Ronggyuan; Njiende, Hugues; Schafmeister, Frank; Ide, Peter (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Resistorless Precharging of Boost PFCs by Phase Angle Control of Thyristors - Schafmeister, Frank; Hufnagel, Michael; Ide, Peter (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Autonomously driven railway cabin convoys — Communication, control design and experimentation - Henke, Christian; Trächtler, Ansgar (2013 International Conference on Connected Vehicles and Expo (ICCVE))

Discrete-time design of adaptive current controller for interior permanent magnet synchronous motors (IPMSM) with high magnetic saturation - Peters, Wilhelm; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

FPGA-based dynamically reconfigurable control of induction motor drives - Buchholz, Oleg; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

Monitoring critical temperatures in permanent magnet synchronous motors using low-order thermal models - Huber, Tobias; Peters, Wilhelm; Böcker, Joachim (2014 International Power Electronics Conference (IPEC-Hiroshima 2014 - ECCE ASIA))

Real-time implementation of an online Model Predictive Control for IPMSM using parallel computing on FPGA - Leuer, Michael; Böcker, Joachim (2014 International Power Electronics Conference (IPEC-Hiroshima 2014 - ECCE ASIA))

Efficiency-optimized Model Predictive Torque Control for IPMSM - Leuer, Michael; Ruting, Arne; Böcker, Joachim (2014 IEEE International Energy Conference (ENERGYCON))

FPGA-based dynamically reconfigurable control of induction motor drives - Buchholz, Oleg; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

Power profile based selection and operation optimization of parallel-connected power converter combinations - Vogt, T.; Peters, A.; Fröhleke, N.; Böcker, Joachim; Kempen, S. (2014 International Power Electronics Conference (IPEC-Hiroshima 2014 - ECCE ASIA))

Voltage sequence control based high-current rectifier system - Solanki, Jitendra; Fröhleke, Norbert; Böcker, Joachim; Duppe, Gregor; Averberg, Andreas; Wallmeier, Peter (2014 IEEE Energy Conversion Congress and Exposition (ECCE))

A completely modular power converter for high-power high-current DC applications - Solanki, Jitendra; Fröhleke, Norbert; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

Ermittlung der Rotortemperatur einer Synchronmaschine mit eingebetteten Permanentmagneten für einen automobilen Traktionsantrieb mittels Beobachter basierend auf elektrischen Größen - Specht, A.

Model-Based Development of DC-DC Converters with Wide Operation Range and High Dynamics - Cao, Z.

Modeling Optimization and Control Design for LCC Resonant Converter Applied in Very Low Frequency High Voltage Generator - Hu, M.

Wirkungsgradoptimale Regelung eines elektrischen Fahrantriebes mit variabler Zwischenkreisspannung - Pohlenz, Daniel

Digital Control for Interleaved Boost Power Factor Correction (PFC) Rectifiers - Grote, T.

Modellprädiktive Regelung permanent erregter Synchronmotoren im Antriebsstrang von Automobilen - Leuer, M.

Evaluierung und Anwendung eines Emulators für elektrische Maschinen in der Entwicklung von Elektro- und Hybridfahrzeugen - Uebener, S.

Traktionsantrieb mit linearem geschalteten Reluktanzmotor für ein autonomes Bahnfahrzeug - Schneider, T.

Die Rolle von Batteriespeichern in KMU-Microgrids - Vogt, T.; Böcker, Joachim; Kempen, S. (BWK – Das Energie-Fachmagazin – Springer VDI Verlag, Ausgabe 12-2014)

Design Considerations on Peak Power Clipping Thresholds in Microgrids - Vogt, T.; Fröhleke, N.; Böcker, Joachim; Kempen, S. (6th World Conference on Photovoltaic Energy Conversion (WCPEC))

Selbstoptimierung in der Anwendung - Böcker, Joachim; Buchholz, Oleg; Romaus, Christoph; Schulte, Christoph; Stille, Karl Stephan Christian (Wissenschaftsforum Intelligente Technische Systeme, 9. Paderborner Workshop Entwurf mechatronischer Systeme)
Die absehbare Entwicklung der Informations- und Kommunikationstechnik wird mechatronische Systeme mit inhärenter Teilintelligenz ermöglichen. Hierfür verwenden wir den Begriff Selbstoptimierung (S.O.). Selbstoptimierende (s.o.) Systeme reagieren autonom und flexibel auf sich ändernde Umfeldbedingungen [ADG+09]. Die Entwicklung derartiger Systeme erfordert eine enge Zusammenarbeit der Entwickler der beteiligten Domänen Mechanik, Elektrik/Elektronik, Regelungstechnik und Softwaretechnik. In diesem Beitrag wird erklärt, wie die Steigerung der Verlässlichkeit durch S.O. bei der Konzipierung eines s.o. Systems adäquat berücksichtigt wird. Die Konzipierung des hybriden Energiespeichersystems des innovativen Schienenfahrzeugs RailCab wird retrospektive durchgeführt. Dies erfolgt von der ersten Funktionsdefinition über die Lösungsauswahl und die dazugehörige Nutzwertanalyse bis hin zur Produktkonzeption des Energiespeichersystems. Es wird gezeigt, wie die Schwachstellen und Widersprüche eines technischen Systems identifiziert sowie mit Hilfe geeigneter Gegenmaßnahmen behoben werden können. Hierbei soll insbesondere die Integration der S.O. als Möglichkeit zur Behebung der Schwachstellen betrachtet werden. Somit wird gezeigt wann und wie die Entscheidung über die s.o. Auslegung des Systems getroffen und die Steigerung der Verlässlichkeit dabei ins Kalkül gezogen wird.
Keywords: Konzipierung; Selbstoptimierung; Verlässlichkeit; Mechatronik; Hybrider Energiespeicher; LEA-Publikation; Eigene

Crosslinked Test Benches - Stille, Karl Stephan Christian; Böcker, Joachim (Design Methodology for Intelligent Technical Systems)
Keywords: Eigene

Online capable optimized planning of power split in a hybrid energy storage system - Stille, Karl Stephan Christian; Romaus, Christoph; Böcker, Joachim (Eurocon 2013)

Self-optimization energy management considering stochastic influences for a hybrid energy storage of an electric road vehicle - Romaus, Christoph; Wimmelbücker, Dominik; Stille, Karl Stephan Christian; Böcker, Joachim (2013 International Electric Machines & Drives Conference)

Wirkungsgradoptimale Arbeitspunktsteuerung für einen permanenterregten Synchronmotor mit vergrabenen Magneten unter Berücksichtigung von Temperatureinflüssen - Wallscheid, Oliver; Böcker, Joachim (ETG-Fachbericht-Internationaler ETG-Kongress 2013–Energieversorgung auf dem Weg nach 2050)

Discrete-time model of an IPMSM based on variational integrators - Specht, Andreas; Ober-Blöbaum, Sina; Wallscheid, Oliver; Romaus, Christoph; Böcker, Joachim (Electric Machines & Drives Conference (IEMDC), 2013 IEEE International)

Two-Phase Interleaving Configuration of the LLC Resonant Converter - Analysis and Experimental Evaluation - Figge, Heiko; Grote, Tobias; Fröhleke, Norbert; Böcker, Joachim; Schafmeister, Frank (Proc. IEEE Annual Industrial Electronics Society Conference (IECON))

Integrated Magnetic for DCM-PSFB Converter - Njiende, Hugues; Li, Rongyuan; Schafmeister, Frank; Ide, Peter

Resonant capacitor clamping circuit in resonant converter - Figge, Heiko; Schafmeister, Frank

Hybrid Energy Storage System (HES) - Stille, Karl Stephan Christian; Romaus, Christoph; Böcker, Joachim (Design Methodology for Intelligent Technical Systems)

Design of a high performance ferrite magnet-assisted synchronous reluctance motor for an electric vehicle - Paradkar, Milind; Böcker, Joachim (IECON 2012 - 38th Annual Conference on IEEE Industrial Electronics Society)

Fast online model predictive control of IPMSM using parallel computing on FPGA - Leuer, Michael; Böcker, Joachim (2013 International Electric Machines & Drives Conference)

Co-simulation of an electric traction drive - Schulte, Christoph; Böcker, Joachim (2013 International Electric Machines & Drives Conference)

Low Latency Hybrid Hardware-in-the-Loop Simulator for Railway Traction System - Tong, Laisheng; Zou, Huanqing; Sun, Meng; Böcker, Joachim (2013 IEEE Vehicle Power and Propulsion Conference (VPPC))

A Novel LC Resonant Based Partial Booster Scheme for Improved Efficiency and Reduced Cost of Transformerless Photovoltaic Inverters - Krishna, D.V.M.M.; Preckwinkel, H.; Fröhleke, N.; Böcker, Joachim (PCIM Europe Conference, Nürnberg, Germany)

Verlustmodellierung und Effizienzoptimierung einer hart schaltenden, netzfreundlichen Pulsgleichrichterstufe (PFC) - Bolte, S.; Baurichter, J.; Henkenius, C.; Fröhleke, N.; Böcker, Joachim; Figge, H. (Internationaler ETG Kongress, Berlin, Germany)

Minimierung niederfrequenter Oberschwingungen in Pulsmustern für 2-Level Umrichter in Antriebssystemen mittels winkelmodulierter Partikel Schwarm Optimierung - Peter, K.; Böcker, Joachim (Internationaler ETG Kongress, Berlin, Germany)

Formaler Regelungsentwurf für netzfreundliche PFC-Ladegleichrichter unter Anwendung eines Netzbeobachters - Keuck, Lukas; Fröhleke, N.; Böcker, Joachim (Internationaler ETG Kongress, Berlin, Germany)

High efficiency photovoltaic power conditioning system - Sharabash, H.; Krishna, D.V.M.M.; Fröhleke, N.; Böcker, Joachim (PCIM Europe Conference, Nürnberg, Germany)

Can oversampling improve the dynamics of PWM controls? - Böcker, Joachim; Buchholz, O. (2013 IEEE International Conference on Industrial Technology (ICIT))

Comparison of Thyristor-Rectifier with Hybrid Filter and Chopper-Rectifier for High-Power, High-Current Application - Solanki, J.; Krishna, D.V.M.M.; Fröhleke, N.; Wallmeier, P. (PCIM Europe Conference, Nürnberg, Germany)

Dynamical modeling for series-parallel resonant converter under optimized modulation - Cao, Zhiyu; Tao, Junbing; Fröhleke, Norbert; Böcker, Joachim (2013 Twenty-Eighth Annual IEEE Applied Power Electronics Conference and Exposition (APEC))

A simplified mathematical model for DC-balancing and capacitor ripple reduction in 3-level inverters - Krishna, D. V. M. M.; Fröhleke, N.; Böcker, Joachim; Preckwinkel, H. (2013 IEEE International Conference on Industrial Technology (ICIT))

A novel low cost solar central inverters topology with 99.2% efficiency - Preckwinkel, Heiko; Bünte, Andreas; Böcker, Joachim; Fröhleke, Norbert; Dora, Krishna (2013 15th European Conference on Power Electronics and Applications (EPE))

A modular multilevel converter based high-power high-current power supply - Solanki, J.; Fröhleke, N.; Böcker, Joachim; Wallmeier, P. (2013 IEEE International Conference on Industrial Technology (ICIT))

A novel space vector modulation strategy for thyristor matrix converters - Lönneker, Michael; Böcker, Joachim (2013 15th European Conference on Power Electronics and Applications (EPE))

Selbstoptimierende Betriebsstrategien für ein hybrides Energiespeichersystem aus Batterien und Doppelschichtkondensatoren - Romaus, C.

Betriebs- und Regelstrategien für den autonomen Fahrbetrieb von Schienenfahrzeugen mit Linearmotor - Henke, C.

A precise open-loop torque control for an interior permanent magnet synchronous motor (IPMSM) considering iron losses - Peters, Wilhelm; Wallscheid, Oliver; Böcker, Joachim (IECON 2012-38th Annual Conference on IEEE Industrial Electronics Society)

Cost-Effective Implementation of a Digitally Controlled LLC Resonant Converter for Application in Server- and Telecom-PSUs - Figge, Heiko; Fröhleke, Norbert; Böcker, Joachim; Schafmeister, Frank (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Novel Hybrid Modulation Schemes Significantly Extending the Reactive Power Control Range of All Matrix Converter Topologies With Low Computational Effort - Schafmeister, Frank; Kolar, Johann (IEEE Transactions on Power Electronics)

Matrixkonverter, Kapitel 3.8 - Kolar, Johann; Schafmeister, Frank (Lehrbuch Leistungselektronische Schaltungen)

Digital Slope Compensation for Current Mode Control - Schafmeister, Frank; Grote, Tobias

Novel dynamical modeling for series-parallel resonant converter - Cao, Z.; Nzeugang, F. H.; Tao, J.; Fröhleke, N.; Böcker, Joachim (21th IEEE International Symposium on Industrial Electronics (ISIE2012), Huangzhou, China)

Reduction of Total Harmonic Distortion (THD)for Interleaved Converters Operating in Discontinuous Conduction Mode (DCM) - Grote, T.; Bolte, S.; Fröhleke, N.; Böcker, Joachim (PCIM Europe Conference, Nürnberg, Germany, 2012)

High Fidelity Hybrid Hardware-in-the-Loop Simulator with FPGA and Processor for AC Railway Traction - Böcker, Joachim; Sun, M.; Cao, Z.; Tong, L.; Zou, H.; Ranjan, P. (PCIM Europe Conference, Nürnberg, Germany)

Full Digital Implementation of an Optimized Modulation Strategy for Series-Parallel Resonant Converter - Tao, J.; Cao, Z.; Sun, M.; Fröhleke, N.; Böcker, Joachim (PCIM Europe Conference, Nürnberg, Germany)

Boosting Dynamics of AC Machines by using FPGA-Based Controls - Buchholz, O.; Mathapati, S.; Böcker, Joachim (PCIM Europe Conference, Nürnberg, Germany)

Analytical and Offline Approach to Select Optimal Hysteresis Bands of DTC for PMSM - Mathapati, Shashidhar; Böcker, Joachim (IEEE Transactions on Industrial Electronics)
Keywords: Electrical and Electronic Engineering; Control and Systems Engineering

Photovoltaic inverter with high efficiency over a wide operation area - a practical approach - Preckwinkel, Heiko; Krishna, DVMM; Fröhleke, Norbert; Böcker, Joachim (IECON 2011 - 37th Annual Conference of the IEEE Industrial Electronics Society)

Time-domain steady-state modeling of series-parallel resonant converter under optimized modulation - Cao, Zhiyu; Tao, Junbing; Fröhleke, Norbert; Böcker, Joachim (IECON 2012 - 38th Annual Conference on IEEE Industrial Electronics Society)

Multi-objective optimization of LCC resonant converter applied in VLF HV generator - Hu, Manli; Fröhleke, Norbert; Peters, Wilhelm; Böcker, Joachim (IECON 2011 - 37th Annual Conference of the IEEE Industrial Electronics Society)

A comparative study of series-parallel resonant converter by using different modulation strategies - Cao, Zhiyu; Nzeugang, Franklin H.; Fröhleke, Norbert; Böcker, Joachim (IECON 2011 - 37th Annual Conference of the IEEE Industrial Electronics Society)

Analysis, design and control of 1MW, high power factor and high current rectifier system - Solanki, Jitendra; Fröhleke, Norbert; Böcker, Joachim; Wallmeier, Peter (2012 IEEE Energy Conversion Congress and Exposition (ECCE))

Optimierte Regelung für mobile Elektromotoren - Wallscheid, Oliver; Peters, Wilhelm; Böcker, Joachim (Aktuelle Technik)

Current controller with defined dynamic behavior for an interior permanent magnet synchronous motor - Peters, Wilhelm; Wallscheid, Oliver; Böcker, Joachim (IECON 2011-37th Annual Conference of the IEEE Industrial Electronics Society)

Digital Control Strategy for Multi-Phase Interleaved Boundary Mode and DCM Boost PFC Converters - Grote, Tobias; Figge, Heiko; Fröhleke, Norbert; Böcker, Joachim; Schafmeister, Frank (Proc. IEEE Energy Conversion Congress and Exposition (ECCE))

Overcurrent Protection for the LLC Resonant Converter with Improved Hold-Up Time - Figge, Heiko; Grote, Tobias; Fröhleke, Norbert; Böcker, Joachim; Schafmeister, Frank (Proc. 26th IEEE Applied Power Electronics Conference (APEC))

Unidirektionaler AC-AC-Matrixkonverter mit Dreipunkt Ein- und Ausgangsstufe - Schafmeister, Frank; Kolar, Johann

Verfahren zum spannungslosen Schalten der Pulswechselrichter-Ausgangsstufe eines indirekten Dreiphasen-AC-AC Matrixkonverters - Schafmeister, Frank; Kolar, Johann

Thermal-electrical modeling and simulation of resonantly operated DC-DC converters based on extended describing function method - Lv, J.; Cao, Z.; Fröhleke, N.; Böcker, Joachim; Yuan, H.; Mi, H. (Proceedings of the 2011 14th European Conference on Power Electronics and Applications)

Control Realization for an Interior Permanent Magnet Synchronous Motor (IPMSM) in Automotive Drive Trains - Peters, W.; Huber, T.; Böcker, Joachim (PCIM 2011, Nürnberg, Deutschland)

Frequency / duty cycle current-mode fuzzy control for LCC resonant converter - Hu, M.; Böcker, Joachim; Fröhleke, N. (EPE2011, Birmingham, UK)